STRATEGI DAN MANAJEMEN PENGELOLAAN RUANG MILIK JALAN PADA RUAS JALAN NASIONAL JAYAPURA-SARMI - Arnold Mika; Harmonis Rante; Dewi Ana Rusim (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
The regional development in Papua is in line with the development of road infrastructure. The Bonggo-Betaf-Sarmi National Road section is a part of the trans-Papua road that crosses several areas, namely Bonggo, Betaf and Sarmi. This road section is the only land route for the economy and government from the capital city of Papua Province, Jayapura City to Sarmi Regency. The area along the road began to develop marked by the construction of buildings on the left and right sides of the road that were designated for settlements, economic activities and stalls. To anticipate the city development and road widening, it is necessary to make an effort to organize and control the buildings that are starting to grow in the Road Owned Space area. This study aims to identify and analyze the existing conditions of the Road Owned Space and develop strategies to anticipate the use of the Road Owned Space by the community. The research location is along Bonggo-Betaf-Sarmi, which is 117.32 km. Data analysis was carried out with qualitative methods. The results indicate that there has been an invasion of the Road Owned Space at several points by the community. To anticipate and stop the encroachment of the the Road Owned Space area, a strategy can be adopted which includes the dissemination of related regulations, socio-cultural approaches and law enforcement.